ANALISIS PERHITUNGAN UPAH LEMBUR KARYAWAN TETAP PADA PT MIGAS MANDIRI PRATAMA SAMARINDA MENURUT SURAT KEPUTUSAN MENTERI TENAGA KERJA DAN TRANSMIGRASI NO. KEP. 102/MEN/VI/2004 - -, Fitriani N. Buluda (EKONOMIA, 2018)
The research method used in this research is descriptive research method by using quantitative approach. And data collection techniques used by researchers are field research and library research. And the analytical tool used is the Decree of the Minister of Manpower and Transmigration No. RI. Kep. 102 / MEN / VI / 2004 article 11.The results concluded that based on the calculation of overtime wages between companies with government regulations in this case the Decree of Minister of Manpower and Transmigration No. Kep. 102 / MEN / VI / 2004 there are differences and differences. PT. Migas Mandiri Pratama does not refer to the Ministry of Manpower and Transmigration Decree no. Kep. 102 / MEN / VI / 2004 in article 11 in determining the calculation of overtime pay, in particular in determining the overtime pay per hour and the calculation of overtime wages made on a normal working day and the excess in working hours. Calculation determined by PT. Migas Mandiri Pratama is lower than the calculation that has been set by the government that has been used as a research tool for analysis.Based on the analysis and calculation of the overtime wages, the proposed hypothesis can be accepted. The hypothesis proposed by the researcher is alleged that the calculation of employees' overtime wage remained at PT Migas Mandiri Pratama not in accordance with the government regulation in this case the Decree of the Minister of Manpower and Transmigration No. RI. Kep. 102 / MEN / VI / 2004.